Is There a Difference in Terms of Perinatal Outcomes Between Fresh and Frozen Embryo Transfers? - Ayse Zehra Ozdemir; Pervin Karli (Medical Network, 2020)
OBJECTIVE: Nowadays, fresh embryo transfers and frozen embryo transfers are frequently employed in the treatment of in vitro fertilization. This study aims to compare the pregnancy outcomes in patients who underwent fresh embryo transfers and frozen embryo transfers. STUDY DESIGN: All patients who underwent fresh embryo transfers and frozen embryo transfers at the in vitro fertilization center, Ondokuz Mayis University between 2010 and 2017 were screened retrospectively and the pregnancy results were evaluated at one-year follow-up. The study included a total of 912 transfers, 679 of which were fresh embryo transfers and 233 were fresh embryo transfers, in 756 patients. Comparisons were made in terms of biochemical pregnancy, clinical pregnancy rate, ongoing pregnancy, and live birth rate. RESULTS: Ectopic pregnancy, biochemical pregnancy, and abortus in fresh embryo transfers were found to be significantly more than that in frozen embryo transfers (p=0.001). However, no statistically significant difference in terms of clinical or ongoing pregnancy rate or live birth rate was observed. Birth weight was significantly lower in fresh embryo transfers than in frozen embryo transfers (p=0.001, p= 0.031). Multiple pregnancies preeclampsia, preterm labor, and placental abruption did not show a statistically significant difference in fresh embryo transfers and frozen embryo transfers. Yet, gestational diabetes was significantly more in frozen embryo transfers (p=0.011). CONCLUSIONS: Early pregnancy complications in fresh embryo transfers are higher than that in frozen embryo transfers. In terms of neonatal results, higher birth weight and gestational diabetes are more prevalent in frozen embryo transfers. In this study, it has been shown that fresh embryo transfers are more often associated with negative pregnancy outcomes. frozen embryo transfers can be better for pregnancy results